Knowledge and awareness of iodine intake - survey among Croatian women of reproductive age - Vidranski, Valentina (Array, 2020)
Introduction: Appropriate iodine intake is important for the entire population, especially in fertile women due to decisive role of thyroid hormones in normal foetal brain development. The aim of this study was to investigate knowledge on iodine role among Croatian women of reproductive age.Materials and methods: The survey was conducted among 378 women of reproductive age during May-September 2018. Data on age, education level, salt intake habits, knowledge of the iodine role and possible presence of thyroid disease were collected and results were presented as numbers or percentage of total number of participants. Comparison between groups was performed by Chi square test.Results: Of 378 participants, 178 reported to be familiar with the iodine role in the body (P = 0.115). Significantly higher proportion of the younger woman and woman with lower degree of education weren’t familiar with the iodine role (P <0.001). More woman were introduced to consequences of insufficient than to excessive iodine intake (273 vs 213; P <0.001). In addition, participants mainly weren’t familiar with obligation of salt iodination (P <0.001). Presence of thyroid disease was recorded in 75 subjects with higher prevalence in subjects 36-49 years (P <0.001). Presence of thyroid disease was not associated with knowledge on iodine role on health.Conclusion: Women of reproductive age are not completely aware of the consequences of excessive iodine intake. Thus, further education focusing on more sensitive groups such as woman of younger age should be considered in order to preserve their and their children’s health.